2017
DOI: 10.5539/hes.v7n1p114
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Web 2.0 Technologies Usage in Programming Languages Lesson on the Academic Success, Interrogative Learning Skills and Attitudes of Students towards Programming Languages

Abstract: It is observed that teacher candidates receiving education in the department of Computer and Instructional Technologies Education are not able to gain enough experience and knowledge in "Programming Languages" lesson. The goal of this study is to analyse the effects of web 2.0 technologies usage in programming languages lesson on the academic success, interrogative learning skills and attitudes of students towards programming languages. "Pre-test-Post-test Control Group Quasi-Experimental Design Model" is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The current situation that was put forward in the first stage showed that a self-efficacy perception of the pre-service IT teachers towards educational software development was low. This finding seems to be compatible with previous research (Gençtürk & Korucu, 2017;Aşkar & Davenport, 2009). In this stage of the research, Computer Programming Self-Efficacy Scale was applied to pre-service teachers.…”
Section: Stage IIsupporting
confidence: 94%
See 2 more Smart Citations
“…The current situation that was put forward in the first stage showed that a self-efficacy perception of the pre-service IT teachers towards educational software development was low. This finding seems to be compatible with previous research (Gençtürk & Korucu, 2017;Aşkar & Davenport, 2009). In this stage of the research, Computer Programming Self-Efficacy Scale was applied to pre-service teachers.…”
Section: Stage IIsupporting
confidence: 94%
“…Previous research focusing on interventions using various tools for changing views or attitudes of learners also indicate that well-designed trainings seem to be successful in this manner (Gençtürk & Korucu, 2017;Yükseltürk & Altıok, 2017).…”
Section: Stage IIImentioning
confidence: 99%
See 1 more Smart Citation